Status of Information and Communication Technology in teacher education the case in Central Visayas, Philippines - Marcial, Dave E. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2016)
Information and Communication Technology (ICT) plays a vital role in teaching and learning. This paper presents the status of ICT competency of the faculty in the teacher education institutions in the Central Region of the Philippines. Specifically, the study investigates the ICT competency level in institutions of higher learning offering teacher education programs in the four provinces in Central Visayas, Philippines. A total of 382 survey responses was analyzed in the study. Respondents are all faculty handling professional and/or specialization courses in the teacher education. The ICT competency level was measured empirically in terms of work aspects described in the UNESCO’s ICT Competency Standards for Teachers. This study reveals that the ICT competency of the teacher education faculty was on the knowledge deepening level, implying integrative, student-centered and collaborative teaching using necessary tools. Hence, there is a slight technology infusion into the teaching instruction among teacher educators. There is a high need to improve the level of competency among the teacher educators, particularly skills in using complex and pervasive ICT tools to achieve innovative teaching and learning.